Visual homing is possible without landmarks: a path integration study in virtual reality - Riecke, Bernhard E.; van Veen, Henricus A. H. C; Bülthoff, Heinrich H (Presence: Teleoperators and Virtual Environments, 2002)
The literature often suggests that proprioceptive and especially vestibular cues are required for navigation and spatial orientation tasks involving rotations of the observer. To test this notion, we conducted a set of experiments in virtual environments in which only visual cues were provided. Participants had to execute turns, reproduce distances, or perform triangle completion tasks. Most experiments were performed in a simulated 3D field of blobs, thus restricting navigation strategies to path integration based on optic flow. For our experimental set-up (half-cylindrical 180 deg. projection screen), optic flow information alone proved to be sufficient for untrained participants to perform turns and reproduce distances with negligible systematic errors, irrespective of movement velocity. Path integration by optic flow was sufficient for homing by triangle completion, but homing distances were biased towards the mean response. Additional landmarks that were only temporarily available did not improve homing performance. However, navigation by stable, reliable landmarks led to almost perfect homing performance. Mental spatial ability test scores correlated positively with homing performance, especially for the more complex triangle completion tasks-suggesting that mental spatial abilities might be a determining factor for navigation performance. In summary, visual path integration without any vestibular or kinesthetic cues can be sufficient for elementary navigation tasks like rotations, translations, and triangle completion.
Keywords: Measurement; Riecke; Riecke_2002; artificial, augmented, and virtual realities; bernhard-riecke; experimentation; human factors; iSpaceWeb; journalPaper; spatial updating; virtual reality